2018
DOI: 10.1186/s13045-018-0646-9
|View full text |Cite
|
Sign up to set email alerts
|

Recombination of a dual-CAR-modified T lymphocyte to accurately eliminate pancreatic malignancy

Abstract: BackgroundThe therapeutic application of T cells endowing with chimeric antigen receptors (CARs) is faced with “on-target, off-tumor” toxicity against solid tumors, particularly in the treatment of the pancreatic cancer. To our best knowledge, the pancreatic cancer cell line AsPC-1 often highly expressed some distinct tumor-associated antigens, such as carcino-embryonic antigen (CEA) and mesothelin (MSLN). Therefore, in this research, we have characterized dual-receptor CAR-modified T cells (dCAR-T) that exert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 36 publications
2
64
0
Order By: Relevance
“…However, there have been several clinical trials involving TAA-targeting CAR-T cells within solid tumors, in which on-target off-tumor recognition of bystander tissue cells has led to life-threatening adverse effects caused by engineered T cells that attack essential normal tissues [6,7]. Therefore, many researchers have attempted to improve the speci city of CAR-T cells; thus, the logic-gated CAR [8,[12][13][14], masked CAR [9], synNotch receptor [10,28,29] and SUPA CAR [11] were developed to reduce on-target off-tumor toxicity. Among these tools, logic-gated CAR-engineered T cells are fully activated only when both a suboptimal CAR and a CCR simultaneously recognize two TAAs on tumor cells, which markedly increases speci city and thus prevents nontumor cells from attacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there have been several clinical trials involving TAA-targeting CAR-T cells within solid tumors, in which on-target off-tumor recognition of bystander tissue cells has led to life-threatening adverse effects caused by engineered T cells that attack essential normal tissues [6,7]. Therefore, many researchers have attempted to improve the speci city of CAR-T cells; thus, the logic-gated CAR [8,[12][13][14], masked CAR [9], synNotch receptor [10,28,29] and SUPA CAR [11] were developed to reduce on-target off-tumor toxicity. Among these tools, logic-gated CAR-engineered T cells are fully activated only when both a suboptimal CAR and a CCR simultaneously recognize two TAAs on tumor cells, which markedly increases speci city and thus prevents nontumor cells from attacking.…”
Section: Discussionmentioning
confidence: 99%
“…Among these tools, logic-gated CAR-engineered T cells are fully activated only when both a suboptimal CAR and a CCR simultaneously recognize two TAAs on tumor cells, which markedly increases speci city and thus prevents nontumor cells from attacking. Nevertheless, recent reports involving logic-gated CARs have shown that two different target antigens, CAR-targeted antigens and CCR-targeted antigens, must be carefully chosen to treat different solid tumors [8,[12][13][14], which is time consuming and laborious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD69 is a standard marker for T-cell activation [20,21]. To demonstrate antigen-specific activation of tan-CAR-transduced T cells, cells from the K562 human leukemia line were transfected with lentiviruses encoding CD19 and/or BCMA in order to generate K562-CD19, K562-BCMA, or K562-CD19+BCMA cells.…”
Section: Tan-car-transduced T Cells Are Activated By Cd19 and Bcma Anmentioning
confidence: 99%
“…In order to overcome antigen escape risk and inter-patient variability, CARs co-targeting two or even three antigens are being developed in several solid malignancies, including breast, pancreatic and brain tumors (110)(111)(112)(113). Conversely, other investigators are testing dual constructs requiring both targets to be expressed on tumor cells in order to exert their cytotoxic activity (114) and inhibitory CARs able to redirect T cells activity from healthy tissues (115), with the aim of increasing CAR specificity and of preventing off-tumor side effects.…”
Section: Car T Cells For Solid Tumorsmentioning
confidence: 99%